Situating Intersectionality - Wilson, Angelia R. author. aut Link
XIII, 215 p.
Keywords: A new generation of political science scholars who are comfortable employing intersectional analysis are emerging and their work hones in directly on the complexity of politics, governance and policy making in an increasingly small, technologically connected, ideologically nuanced, global Public Square.